Love of Money, Religiosity, and Gender: How do These Affect the Ethical Perceptions of Public Accountants? - Saadah, Naili; Samroh, Samroh (Universitas Negeri Semarang, 2021)
Ethics has always been an interesting issue to discuss in any discussion related to the professionalism of the world of accounting and auditing. Public scepticism towards the accounting profession is quite reasonable since there are not a few auditors and public accountants involved with financial scandals. Money for an individual is like a double-edged knife, on the one hand, it is a need, but it can also be a root of greed, no exception for an auditor. Therefore, this study aims to determine the effect of love of money on the ethical perceptions of public auditors. Whether there is an influence of the love of money on the ethical perceptions of public auditors and how does this affect it when faced with one’s religiosity and gender. Using the object of the research of auditors who are members of the public accounting firm in Semarang city, this research succeeded in collecting a sample of 43 auditors with the criteria of having had at least three years of experience as an auditor. The results prove that love of money has a direct effect on the ethical perceptions of public auditors. However, when the feeling of love of money is faced with religiosity and gender, it does not significantly influence auditors’ ethical perceptions. Therefore, it can be concluded that love of money is one’s attitude in general which is reflected in the behaviour of an auditor so that one’s love of money can directly influence an auditor’s ethical perception. Keywords: Love of Money; Religiosity; Gender; Ethical Perceptions